PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) MENGGUNAKAN LIVEWORKSHEET PADA MATERI SISTEM GERAK KELAS XI SMA NEGERI 2 JENEPONTO - Nurul Ariska; Abd. Haling; Pattaufi (STKIP Subang, 2023)
The problem in this study is that the concentration of students is lacking in learning activities because the teaching materials used by educators are not varied with a wide range of material descriptions which have an impact on students being less active in learning because they do not understand and master the learning material. Not in accordance with the 2013 curriculum which requires student-centered learning (student center). The aims of this study were to 1) analyze the needs of E-LKPD products, 2) determine the validity level of E-LKPD products, 3) find out the practicality of E-LKPD products. This research was conducted using a Research and Development (R&D) approach and type of research using the ADDIE development model. The subjects of this study were 25 students and two biology teachers. Data collection techniques using interviews and questionnaires. The results of this study indicate that 1) the identification of the level of need for the development of the E-LKPD is in the required qualifications, 2) The results of testing the validity of the E-LKPD teaching materials by content/material experts obtained an average total value of 95% which is in a very valid qualification and validation results by design/media experts obtained an average total score of 87% in very valid qualifications, 3) The results of the practicality test conducted on two biology tutors obtained an average total score of 99% in very practical qualifications and trials on class XI MIA 1 students consisting of 25 students obtained a total average score of 94% which is in a very practical qualification. Based on the results of this analysis it can be concluded that the teaching materials for Electronic Student Worksheets (E-LKPD) are valid and practical to use in the learning process.